Connecting to learn : educational and assistive technology for people with disabilities - Scherer, Marcia J. 1948- (American Psychological Association, 2004)
(from the jacket) This book is a comprehensive approach to matching the right assistive technology with students with disabilities, especially visual and auditory disabilities. The author explores the way disabilities, especially those involving the senses, can lead to isolation and a lack of "connectedness," and how this leads to educational difficulties. A step-by-step model for assessing and evaluating the needs of individual students and finding the right assistive technology to hep each student, is provided. This book features data on prevalence of vision and hearing loss as well as quotations from students and teachers about the various technologies they use in their schools and in daily life.